Augmented Reality Nursery In Hand Application - Neeshallini, Manimaran (2023)
Growing plants may be a hobby and interest for many people but it has become a hard process in recent years as everyone is starting to live a busy life and tend to forget about their plants resulting in the plants not surviving. As a solution to this problem, this Augmented Reality (AR) application can be used by them before purchasing a plant. This AR application is very handy as it can be used from anywhere if a smartphone and flashcards are present. From this application, knowledge on how to care for the plant can be obtained and could result in longer and healthier plant life. Through this application many of those who have lost interest in growing plants could regain their interest by choosing the right plan for them as growing them is also stated to be therapeutic and releases stress. The methodology adopted in this project is the ADDIE model, which makes the project development more organized. The AR application is developed using Unity Engine and Vuforia Engine while is designed using Photoshop. The simple interface allows users to focus more on the delivered content and achieve the goals of this project. After the project is completed, there will be playtesters to evaluate the project using the User Acceptance Test (UAT).